2009
DOI: 10.1007/s11136-009-9474-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life assessment among haemodialysis patients in a single centre: a 2-year follow-up

Abstract: There was improvement of QOL mental domains over time. However, the physical aspects improved only in low-comorbidity patients. More women than men worsened regarding physical functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
(19 reference statements)
3
15
1
1
Order By: Relevance
“…as the age increases, patients' physical and mental health function decreases. Several other studies [8,[13][14][15][16]] also goes along with the above findings that the low scores on QOL was related to older age. Regarding the gender factor, female patients were found to have low QOL than those of the male patients (p<0.05).…”
Section: Discussionsupporting
confidence: 53%
“…as the age increases, patients' physical and mental health function decreases. Several other studies [8,[13][14][15][16]] also goes along with the above findings that the low scores on QOL was related to older age. Regarding the gender factor, female patients were found to have low QOL than those of the male patients (p<0.05).…”
Section: Discussionsupporting
confidence: 53%
“…Gender did not have a significant influence on the V-RQOL Questionnaire, which confirms the data in the literature [5,6,16,30] . In contrast to other diseases [31,32] , the subjective burden elicited by dysphonia is not perceived differently by women and men. This is important with regard to methodological aspects, as the V-RQOL Questionnaire [20][21][22] does not have to be evaluated in a gender-specific way [33] .…”
Section: Discussionmentioning
confidence: 64%
“…Time on dialysis was independently associated with a better HRQoL in all dimensions studied. For instance, prospective studies in HD populations have demonstrated an improvement on HRQoL over time [9,38]. Higher hemoglobin levels were associated with better physical HRQoL.…”
Section: Discussionmentioning
confidence: 99%